Long-term effects of therapeutic exercise on nonspecific chronic neck pain: a literature review - Cheng, Chih-Hsiu; Cheng, Hsin-Yi Kathy; Yen, Ling-Wei; Su, Hao-Tsung; Liu, Wen-Yu (Journal of Physical Therapy Science, 2015)
[Purpose] Nonspecific neck pain is a common musculoskeletal disease. Therapeutic exercise has been shown to improve pain and disability in short-term and midterm follow-ups. This study performed a literature review of the long-term effects of therapeutic exercise on subjects with nonspecific chronic neck pain. [Subjects and Methods] The databases of the CINAHL, MEDLINE, PEDro and PubMed were used. Randomized controlled trials (RCT) published from January 2000 to January 2014 and explicitly including a one-year follow-up were identified. [Results] Only six articles were included in this review. They had scores of 5 to 8 points on the PEDro scale, and the level of evidence was grade I. The study results show that the main exercises used were cervical strengthening and endurance training exercise. Short-term exercises (10 to 12 weeks) helped to improve the body function, structure, activity and participation immediately after the intervention, but not at the long-term follow-up. On the other hand, long-term interventions (1 year) resulted in improvements in body function and structure at the 3 year follow-up. [Conclusion] The results of the six high-quality studies suggest that long-term exercise have long-term benefits for patients with nonspecific neck pain in terms of body function and structure.